Cell surface expression of human RP105 depends on N‐glycosylation of MD‐1. Issue 24 (28th July 2022) - Biswas, Mrityunjoy; Yamazaki, Tatsuya; Tomono, Susumu; Karnan, Sivasundaram; Takagi, Hidekazu; Ichimonji, Isao; Inui, Masanori; Nagaoka, Fumiaki; Hosokawa, Yoshitaka; Akashi‐Takamura, Sachiko
Abstract : For its cell surface expression, radioprotective 105 (RP105) – an orphan Toll‐like receptor – must form a complex with a soluble glycoprotein called myeloid differentiation 1 (MD‐1). The number of RP105‐negative cells is significantly increased in patients with systemic lupus erythematosus (SLE); however, to elucidate the mechanism underlying this increase, how RP105 is expressed on the cell surface depending on MD‐1 should be investigated. We demonstrated that RP105 exhibits two forms depending on MD‐1 and its two N ‐glycosylation sites, N96 and N156. Cell surface expression of RP105 decreased in the presence of mutant MD‐1 (N96Q/N156Q). Nonglycosylated MD‐1 decreased the de novo cell surface expression of RP105 but not pre‐expressed RP105. Thus, the N ‐glycans of MD‐1 may represent targets for SLE therapy. Abstract : Cell surface expression of RP105—a TLR family protein—requires a soluble glycoprotein, MD‐1, which has two N ‐glycosylation sites—N96 and N156. We showed that RP105 exhibits two forms, the U and L forms, depending on the N ‐glycans of MD‐1. Cell surface expression of RP105 was reduced in the presence of mutant MD‐1 (N96Q/N156Q).